9 months that count forever : how your pregnancy diet shapes your baby's future - Inchauspé, Jessie (Simon Element, 2026)
"From bestselling author and Glucose Goddess, a groundbreaking guide to the science of pregnancy nutrition that empowers mothers-to-be to improve their baby's health for a lifetime. Most pregnant women are told: "Eat whatever you normally eat. Your baby will get what he needs from you." But science tells a different story: your diet during pregnancy shapes your baby's health for life. And somehow, no one has told you the rules--until now. When biochemist Jessie Inchauspé became pregnant, she uncovered striking research: choline, DHA, protein, and glucose are four key nutrients that influence a baby's development in the womb; yet most women don't get nearly enough of the first three and too much of the fourth. In this book, Jessie reveals science-based hacks to: Support your baby's brain development, cognitive growth, and emotional resilience ; Help lower their risk of health challenges later in life like asthma, allergies, and diabetes ; Influence your baby's body composition, organ function, and long-term metabolism. With guidance on supplements, nausea, labor, breastfeeding, meal plans, and recipes, as well as Jessie's personal journey, this book reveals the extraordinary power mothers hold during pregnancy--and is an essential companion for every parent-to-be"--